Adapting to Remote Work: Emerging Cyber Risks and How to Safeguard Your Organization (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2025)
The COVID-19 pandemic has rapidly accelerated the shift to remote work, permanently altering organizational dynamics. As businesses and employees adapted to a remote-first environment, they also became exposed to a new set of cybersecurity threats. The traditional cybersecurity measures designed for office environments are no longer sufficient to address the unique risks associated with remote work. These risks include vulnerabilities in home networks, unsecured devices, increased susceptibility to phishing and social engineering attacks, and the rapid adoption of cloud-based collaboration tools. This paper will explore the cybersecurity challenges posed by remote work and suggest proactive steps organizations can take to safeguard their data, assets, and personnel. Key strategies, including enhanced endpoint security, secure communication channels, Multi-Factor Authentication (MFA), security awareness training, and Zero Trust architecture, will be discussed to help organizations minimize their exposure to these emerging risks.